Ontological characterization of the photosynthesis concept and epistemological and ontological obstacles related to the teaching this concept - Luiz Fabio Dimov (Investigações em Ensino de Ciências, 2014)
The present study focus in the ontological characterization of the photosynthesis concept and epistemological and ontological obstacles that are present during the teaching of this concept. We considered that an individual can express himself/herself in different ways of speech and thinking about a particular concept and apply it in many contexts. Based on ideas related to conceptual profile, we analyzed the data that we obtained from the development of a sequence of activities about the concept of photosynthesis that valued interactionism. In this study we had the following objectives: (I) propose in which ontological subcategory of Process the photosynthesis concept belongs; and (II) to identify and to analyze epistemological and ontological obstacles that are present during the learning process of the photosynthesis concept. To achieve our first objective, we characterized the concept according to the properties of the Equilibration process, and we concluded that photosynthesis is this sort of process. To contemplate our second aim, we developed and applied a sequence of activities about photosynthesis. This activity was applied in different groups of students and it was recorded audio and video. After we selected a group of five students, we transcribed the discursive interactions and we realized a microgenetic analysis of the mutual influences of these individuals during the activities. From this analysis we identified seven obstacles that could difficult the process of teaching and learning of the concept. In the context of cleaning and air renewal, we identified four obstacles. The first one has ontological character and it relates to the attribution of features from Events to Equilibration. The other three were classified as epistemological obstacles: pragmatic; primary experience, and general knowledge. In the context of the gases that are involved in photosynthesis process, we discussed a verbal epistemological obstacle and another one from the general knowledge. The last obstacle has as theme the importance of the glucose for the living beings and it was also related to an epistemological obstacle from the general knowledge.